Effect of topical simvastatin (1.2 mg) on gingival crevicular fluid interleukin-6, interleukin-8 and interleukin-10 levels in chronic periodontitis - A clinicobiochemical study - Harpreet Singh Grover; Shalini Kapoor; Ajita Singh (Elsevier, 2016)
Objectives: The impact of simvastatin (SMV), a cholesterol lowering drug, on bone metabolism appears to involve complex interaction with cholesterol metabolites, hormones, inflammatory mediators and growth factors, thus having direct influence on extent and severity of periodontitis. The present study aims to evaluate the in vivo effect of subgingivally delivered SMV gel (1.2 mg) as a local drug-delivery agent on clinical parameters and on interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-10 (IL-10) levels in gingival crevicular fluid (GCF) of chronic periodontitis patients. Materials and methods: 50 patients were selected and categorized into two treatment groups: control (scaling and root planing) and test group (scaling and root planing with SMV gel). At initial appointment, clinical parameters were measured. Biochemical analysis of GCF samples was done to evaluate the amount of IL-6, IL-8 and IL-10. GCF sampling and clinical parameters were repeated at one and three months for both the groups. Results: SMV has an inhibitory effect on pro-inflammatory cytokines (IL-6, IL-8) and stimulatory effect on anti-inflammatory cytokines (IL-10) in GCF of periodontitis patients and has significantly positive effect on all clinical parameters except relative attachment level (RAL). The addition of SMV, thereby, further alters the levels of cytokine that reflect enhanced antibacterial host defence activity at that site. Conclusion: Topical SMV has a beneficial effect on periodontal health. Removal of the bacterial plaque and subgingival delivery of SMV significantly modulates the chemokines present in GCF. To summarize, SMV shows promising role in the management of periodontitis.